WEIERSTRASS AND BLASCHKE TYPE FUNCTIONS - Mikaelyan, G. V.; Mikaelyan, Z. S. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2010)
In the present paper the Weierstrass multipliers are generalized and the theorem of convergence of corresponding infinite products is proved. Representations of Blaschke type functions are established through Weierstrass type functions and Blaschke function. A way construction of new Blaschke type products is shown, and a method of proof of their convergence is developed. Some relations between Blaschke type products are established.